Penggunaan Model Pembelajaran Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar Siswa Kelas V Sekolah Dasar: The use of the Numbered Head Together (NHT) Learning Model to Improve the Learning Outcomes of Class V Elementary School - Rahmah, Siti; Marlina, Marlina; Saufi, Muhammad (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
This research is classroom action research carried out in four stages, namely planning, implementation, observation, and reflection. This research aims to improve the science learning outcomes of fifth-grade students at Muhammadiyah Elementary School, who met 20 people consisting of 11 men and 9 women. Data collection was carried out using tests and observations. The research instruments used were test items on student learning outcomes and observation sheets of teacher and student activities. The results of this study stated that there was quite a good improvement, completeness in cycle I of meeting 2 was 50% complete, while in cycle II of meeting 2 completion reached 90%. Based on these data, it can be concluded that using the Numbered Head Together learning model can improve the science learning outcomes of Class V Muhammadiyah Elementary School students.